2011
DOI: 10.1002/jcc.21966
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation on redox‐switchable second‐order nonlinear optical responses of push–pull Cp*CoEt2C2B4H3‐expanded (metallo)porphyrins

Abstract: The second-order nonlinear optical (NLO) properties of the Cp*Co(C(2)H(5))(2)C(2)B(4)H(3)-expanded (metallo)porphyrins (Cp* = C(5)Me(5)) have been investigated by using ab inito RHF and density functional theory (DFT) methods. The investigation shows that the compound with expand porphyrin possesses remarkable large molecular hyperpolarizability β(tot) value, ~414.1 × 10(-30) esu (at LC-ωPBE level), and might be an excellent second-order NLO material. From the character of charge transfer (CT) transition, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Alongside the laboratory and spectroscopic techniques now accepted as suitable for the characterization of novel NLO materials, computational methods (including semiempirical methods and ab initio and density functional theory, DFT) have become an increasingly powerful and versatile tool. DFT, in particular, appears very well suited to the modeling and exploration of large TM-containing systems, while electronic excitation spectra and response properties can be assessed using time-dependent DFT (TD-DFT).…”
Section: Introductionmentioning
confidence: 99%
“…Alongside the laboratory and spectroscopic techniques now accepted as suitable for the characterization of novel NLO materials, computational methods (including semiempirical methods and ab initio and density functional theory, DFT) have become an increasingly powerful and versatile tool. DFT, in particular, appears very well suited to the modeling and exploration of large TM-containing systems, while electronic excitation spectra and response properties can be assessed using time-dependent DFT (TD-DFT).…”
Section: Introductionmentioning
confidence: 99%
“…24,25 This functional has been used for several studies of similar systems and shown to provide accurate results. [26][27][28][29][30] Optimization and frequency calculations of the lowest energy conformation of each structure were repeated using the same functional in conjunction with a correlation consistent, double zeta basis set (cc-pVDZ) to further validate results. Both basis sets produced structures that are in excellent agreement with X-ray crystal data, with Co-N and Co-O bond distances differing by less than 2 or 3% for calculations performed with 6-31G(d) and cc-pVDZ, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the topic of NLO responses for molecular switches ranges from the organic molecules to the organometallic molecules. Compared with the organic molecules, organometallic molecules associated with a metal center interacting with organic ligands have the unique structural and electronic characteristics [10].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the topic of NLO responses for molecular switches ranges from the organic molecules to the organometallic molecules. Compared with the organic molecules, organometallic molecules associated with a metal center interacting with organic ligands have the unique structural and electronic characteristics [10].Remarkably, switching of NLO responses [11e15] can be achieved by photoisomerization, redox, and protonation and so forth. The researches on photo-switchable NLO properties of photochromic compounds have received much attention [16,17].…”
mentioning
confidence: 99%